Electroacupuncture Exerts Anti-Obesity Effects by Affecting the Gut Microbiota and Upregulating Acetic Acid and 5-HT Levels in Obese Rats - Zhang J; Yang C; Xiong J; Qian H; Xie Y; Xie S; Luo Y; Yu J; Yu H; Xu J (Diabetes, Metabolic Syndrome and Obesity)
Jie Zhang, Chun Yang, Jian Xiong, Hongyu Qian, Yuanyuan Xie, Shunkai Xie, Yi Luo, Jianhong Yu, Hai Yu, Jing Xu College of Acupuncture and Tuina, Chengdu University of Traditional Chinese Medicine, Chengdu, 610075, People’s Republic of ChinaCorrespondence: Jing Xu, Email xujing@cdutcm.edu.cnBackground: Obesity is a highly prevalent metabolic disorder that significantly increases the risk of cardiovascular and cerebrovascular diseases. Acupuncture has demonstrated remarkable efficacy in treating obesity, offering substantial societal health benefits.Objective: Electroacupuncture has shown promise in the treatment of obesity (OB). The development of obesity is directly linked to the gut microbiota. Therefore, we aimed to explore the mechanism by which electroacupuncture alleviates obesity induced by a high-fat diet (HFD) by modulating the gut microbiota.Methods: Fifty specific pathogen-free Sprague–Dawley (male) rats were obtained, and 44 rats were randomly selected and subjected to an HFD. The remaining six rats were used as controls and subjected to a basic diet. The successfully-induced-obese rats were randomly divided into four groups: the obese group (n=6), the obese+electroacupuncture group (n=6), the obese+antibiotic group (n=6), and the obese+antibiotic+electroacupuncture group (n=6). Furthermore, the weight-reducing effect of electroacupuncture was investigated in HFD-induced obese rats by monitoring their body weight, food consumption, Lee’s index, blood fat, and liver steatosis. The levels of 5-hydroxytryptamine (5-HT), gut microbiota composition, and short-chain fatty acid content were measured and characterized.Results: Electroacupuncture significantly reduced body weight in obese rats and alleviated lipid metabolism disorders. Furthermore, it also improved the number, abundance, and structure of the gut microbiota in obese rats and increased acetic acid and 5-HT content. Moreover, Lactobacillus faecis (L. faecis) and Bacteroides fragilis (B. fragilis) were correlated with obesity-related indicators, acetic acid levels, and 5-HT content.Conclusion: Electroacupuncture may exert anti-obesity effects by modulating acetic acid levels and 5-HT release by intestinal enterochromaffin cells. L. faecis and B. fragilis in the gut microbiota may be potential targets for the treatment of obesity in the future.Keywords: obesity, electroacupuncture, gut microbiota, acetic acid, 5-HT